2014
DOI: 10.1002/anie.201311009
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Rhodium(I)‐Catalyzed Activation of Enantiotopic Cyclobutanone CC Bonds

Abstract: The selective functionalization of carbon-carbon σ bonds is a synthetic strategy that offers uncommon retrosynthetic disconnections. Despite progress in C-C activation and its great importance, the development of asymmetric reactions lags behind. Rhodium(I)-catalyzed selective oxidative additions into enantiotopic C-C bonds in cyclobutanones are reported. Even operating at a reaction temperature of 130 °C, the process is characterized by outstanding enantioselectivity with the e.r. generally greater than 99.5:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(33 citation statements)
references
References 91 publications
0
30
0
3
Order By: Relevance
“…It has been observed that both chemo- and stereo-selectivities are difficult to control in these otherwise elegant reactions, likely due to the high reactivity of the metal catalyst and the metal-bound intermediates. 6 , 7…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that both chemo- and stereo-selectivities are difficult to control in these otherwise elegant reactions, likely due to the high reactivity of the metal catalyst and the metal-bound intermediates. 6 , 7…”
Section: Introductionmentioning
confidence: 99%
“…Carbometallation could occur with the opposite regioselectivity to generate 5 , which upon reductive elimination would yield bicyclic heptanones 6 (Figure 1c-route B). 15a On the basis of our previous study, 13 we realized that the key challenge would be to identify a catalyst to favor the proposed cycloisomerization, in preference to the known hydroacylation and carboacylation 15 pathways.…”
mentioning
confidence: 99%
“…This observation is likely to have wider implications given the emerging family of processes that are dependent upon this key mechanistic step. 8b , 13 , 14 Current studies are focused upon the development of other medium-ring methodologies inspired by the mechanistic insights gained here.…”
mentioning
confidence: 99%